Efeitos de florestas ripárias em restauração na estrutura de comunidades de macroinvertebrados aquáticos e nas taxas de decomposição de matéria orgânica - Giraldo Hernández, Carolina (2018)
Riparian forests play a very important role in protecting watercourses and represent an energy source for the aquatic communities in low-order streams. Therefore, the input of allochthonous material from these ecosystems influence the food chains and create microhabitats that influence the composition and spatial distribution of aquatic macroinvertebrates. These organisms, in turn, are responsible for incorporating plant material into the secondary production and for decomposing the organic matter. Therefore, restoration of riparian vegetation, although frequently performed at a small spatial scale, may have positive effects on aquatic biota. This study evaluated the effects of riparian forests under restoration on the structure of aquatic macroinvertebrate communities and on the rates of organic matter decomposition in low-order streams in southeastern Brazil. Three types of streams were compared, 1) with natural riparian forest, 2) with riparian forest under restoration, and 3) with riparian zones altered by anthropic activities. Within each stream, a 150 m reach was selected to study the substrate characteristics of the streambed (small spatial scale), riparian forest (intermediate scale) and land use and occupation of the basin (large scale). Streams under restoration were intermediate between the agricultural and natural streams in relation to the composition of aquatic macroinvertebrates, showing that riparian forests under restoration have positive effects on the diversity of aquatic communities. Although restoration did not have a positive effect on organic matter decomposition rates, current velocity had a significant effect, being higher in the agricultural streams, suggesting that other factors at different spatial scales, modulated by the proportion land cover by riparian forests, can influence this ecosystem function through complex interactions.